Australian maternity care, considering risk and supporting safety: A scoping review. (September 2022) - Brundell, Kath; Vasilevski, Vidanka; Sweet, Linda
Highlights: Maternity service tolerance for risk can be impacted by a propensity to view birth as complex. Chief Executive Officer (CEO) attrition within health services impacts consistency in quality and safety priorities. Executive perspective of senior midwifery leadership as a driver of operational safety and maternity service sustainability requires further research. Rural maternity service closures have the ability to generate risk for women and negatively impact families with associated travel, financial, and emotional burdens. Abstract: Objective: Assessment of women's risk status influences the operationalisation of maternity. Decisions are made at a health service executive level, related to the ongoing level of maternity care provided, and/or sustainability of the maternity service. The aim of this scoping review was to explore how health service executives considered maternity risk when operationalising safe maternity services in Australia. Design: Scoping review methodology was used to examine the breadth and extent of evidence, and to identify potential gaps in the research evidence. Results: Overall, there was little literature on how health service executives understand and interpret risk to providing and operationalising maternity services. Evidence indicated a reduced tolerance for risk in the provision of maternity services. Executive consistency and midwifery leadership were important in operationalisation of maternity service provision. Key conclusions: With rising rates of maternity service closure and reduction of service capability in Australia, women are most impacted, having reduced access to timely and quality care. More needs to be done to understand the health service executive perspective regarding drivers for these decisions and the barriers and enablers for maternity service sustainability. How health service executives perceive maternity care and experience operationalising maternity services, particularly in rural areas is a gap identified. Further research is warranted in this area to address this significant lack of knowledge. Implications for practice: Understanding how health service executive consider maternity care is crucial for ongoing operational safety and maternity care sustainability.